Grandmothers' picnic at Chase Ranch on the Ponil (Cimarron, NM, 1912)
Grandmothers' Picnic at the Chase Ranch on the Ponil about 4 miles northwest of Cimarron.
Black and White photographs - From the Collection of Victor Grant
Master list item #: 1
File location is in the Raton file Cabinet
Keywords: Lambert, Mary; Chandler, Mrs. George; Crocker, Mrs. Frank; Chase, Nettie; Hoover, Katherine; Funke, Mrs. Heman; Whiteman, Mrs. Rufus; Masten, Mrs; Lodge, Mrs; Cartwright, Mrs. W M; Curtis, Mrs Zenas; Rivingston, Mrs. Jim; Rupert, Mrs. Gertie; Vance, Mrs; Chase Ranch; Picnic Photographs; Ranch Photographs; Female Photographs; Ponil Creek; Cimarron; New Mexico